Territory of Alaska, northwest section / Treasury Department, U.S. Coast and Geodetic Survey - U.S. Coast and Geodetic Survey (Washington, D.C. : United States Coast Survey, 1900)
Relief shown by hachures and spot heights. Color 1:1,200,000